GLOBALISASI DARI PERSPEKTIF KRITIS - Lailiy Muthmainnah (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
By the end of the twentieth century the meaning of globalization were contested in every where. Not only in the economic or political debate, but it is also in the media. There are two major questions about globalization. Is that unavoided process or just an ideological project from the owner of social power in the world? Critical perspective said that world order not only as a product from the relations between one’s states to the others but also product from the relations between social powers in the world. Include at this point are material, ideological, and institutional power. And the world order formed by the configuration of it. So, in the critical perspective, globalization isn’t a natural or given reality, because any dominant actor in this project. And this actor uses their social power to directing where the globalization goes on. Unfortunatelly, no one’s (states) try to struggle from this condition. They just keep silent in this hegemonic process. The last question is how to solve this problem? And Antonio Gramsci said that war of position and war of maneuver are the ways to solve this problem.